Analysis of Radar Cross Section Reduction of Fighter Aircraft by Means of Computer Simulation - Andrade,Luiz Alberto de (2014)
ABSTRACT: This paper presents a preliminary study of the Radar Cross Section (RCS) reduction on the fighter aircraft. First, it was studied the RCS of the aircraft from computational simulations based on prior knowledge of vulnerable areas of this aircraft to radar threats. Subsequently, the possible applications of Radar Absorbing Materials (RAM) on the surface of the aircraft were evaluated, in order to reduce its RCS. The absorber material used in the simulations was denominated FC70, which has good attenuation in the range of 10 to 12 GHz. The study of this reduction was accomplished by applying RAM in four different scenarios at the frequency of 11.1 GHz, where the material is more sensitive. The RCS simulations of the fighter aircraft and its RCS reduction by RAM application were carried out with the support of the software "Computer Simulation Technology" (CST), version 2012. Such technology makes it possible to simulate the application with an absorber material layer on the surface of the aircraft. For the study of the RCS reduction on the fighter aircraft, it was first necessary to develop a detailed 3D model of the fighter aircraft, and it was developed with the software "Computer Aided Three-Dimensional Interactive Application" (CATIA). In conclusion, it is impossible to make much progress attempting to retrofit stealth onto a conventional aircraft because if the shape is wrong, no amount of absorbing material treatments will reduce the RCS.